Antibacterial Activity of Lactic Acid Bacteria From Chao Pangkep Against The Growth of Pathogenic Bacteria Methicillin-Resistant Staphylococcus Aureus (MRSA) - Ade Irma; Juniati Binti Lukman; Nur Insani Amir; Arafah Nurfadillah (Universitas Pekalongan, 2025)
Chao is a traditional fermented food that comes from the Pangkep area. The microorganism that dominates Chao is the lactic acid bacteria (LAB). LAB bacteria belong to a group of probiotic bacteria that have many health benefits. Methicillin-Resistant Staphylococcus aureus (MRSA) bacteria are bacteria that cause infections whose prevalence is increasing. The purpose of this study is to explore LAB from Chao Pangkep as a new source to find LAB that can be used to treat MRSA infection. The research methods carried out were LAB isolate rejuvenation, lactic acid bacterial selection through hemolytic tests and antibacterial activity tests using the agar diffusion method (Kirby and Bauer disc diffusion). The test results showed that three LAB isolates, namely C2, C10, and C11, were γ-hemolytic (non-hemolytic) so they were not pathogenic. The three non-pathogenic isolates were subsequently used as LAB candidates for testing antibacterial activity. Antibacterial activity is shown by the presence of clear zones formed around bacterial colonies. The existence of LAB's ability as an antibacterial is due to the production of metabolite compounds. Therefore, the lactic acid (LAB) bacterial isolate with code C11 has antibacterial activity, so it can be used as a potential candidate to control pathogenic bacteria.